Desain Kurikulum Perguruan Tinggi Pesantren dalam Mewujudkan Pendidikan yang Bekualitas - Firdaus, Fauzan Akmal; Husni, Husni (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2021)
Curriculum is one of the important components that play a role in the process of implementing education for higher education level. In the implementation there are several obstacles, among others, changes in the curriculum system that require educators to master the new system and learners must master the material according to the target of maximum achievement in learning. From these problems, it is necessary to develop a curriculum that integrates the government-defined curriculum and the internal curriculum of institutions developed autonomously by their respective institutions. The purpose of this research is to produce a product guidebook for the design of the curriculum of pesantren universities and its application to STIABI Riyadlul 'Ulum to realize a quality education. The research method used is Research and Development (R& D) and the hypothesis of this research is the effectiveness of the college curriculum design manual pesantren in the academic process of lectures. The method used consists of interviews, tests, questionnaires and written documentation, in analyzing the data, researchers use the t-test formula. The results showed that the implementation of the curriculum design of pesantren universities in realizing quality education has an influence on curriculum development. This can be seen from the T-Test i.e. the T-Count score (t) in this study (-5,591) is greater than the T-Table (2,064). From the results of the t-test, the researchers concluded that the research hypothesis in this study is acceptable. This is evidenced from the significant value of p-value 0.000 (p < 0.05) meaning that there is an influence given from the design of the curriculum of pesantren universities to realize a quality education.